Efektifitas Model Pembelajaran Inkuiri Berbantuan Media Petaku Terhadap Hasil Belajar Matematika - Ramadhani Putri Praswanti; Henry Suryo Bintoro; Himmatul Ulya (Program Studi PGSD, Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2020)
The purpose in this study is to know the improvement of learning outcomes aspects of knowledge, and skills namely student activities, and achievement of minimum completeness criteria in the implementation of inquiry models with petaku media on the skala theory. This research was conducted in two elementary schools in the Kudus country. Sample in this research totaling 67 students, includes experimental and control class and conducted in three meetings. There are two variables, the independent variable is inquiry learning model with colaboration petaku media, and the dependent variable used is student learning outcomes in aspect of knowledge and students learning activities. The research is an experimental quantitative. The results showed that there was an increase in mathematics learning outcomes before and after the implementation of the inquiry learning model, which was indicated N-Gain test with increase of 0,69 and included in the category of moderate improvement. Students activities taught experimental class and control class there is also a difference, with a significance value that appears in the Mann-Whitney test that is equal to 0,037 which can be interpreted that learning activities in the experimental class are better than the control class. Learning ini experimental class also reached the classical and individual completeness criteria, the result of individual learning completeness indicated by the One-Sample TTestwith a significance level of 0.001, more than 75% of the students completed.Keywords: Inquiry model, mathematics achievement, Petaku media